Ethnobotanical survey of the Ferghana and Andijan regions of Uzbekistan - Khojimatov, O.K.; Khamraeva, D.T.; Kosimov, Zokir Z.; Bussmann, Rainer W (Ethnobotany Research and Applications, 2025)
Background: This paper provides information on medicinal plants used by the local population of Ferghana and Andijan regions. Methods: Data were collected during the 2022 and 2023 surveys as a result of interviews, rapid assessments, and the collection of field materials. Interviews with the local population were conducted in the form of a questionnaire, with the consent of the informants. Results: During ethnobotanical studies conducted in the Fergana region, a total of 230 ethnobotanical records were documented regarding the use of plants by the local population. These records encompass 182 species belonging to 77 genera from 7 families. The 20 most frequently mentioned species are presented in Table 5. Similarly, our research in the Andijan region documented the use of 125 medicinal plant species belonging to 77 genera from 20 families. A total of 215 ethnobotanical records were collected, with the 18 most frequently mentioned species summarized in Table 5. Conclusions: In the Ferghana region, of the most commonly used medicinal plants, the families Asteraceae (60.6%) and Lamiaceae (19.4%) are of leading importance, and the genera Artemisia L. (17/22.1%) and Ferula L. (13/16.8%) are distinguished by the largest number of species with medicinal properties. According to collected data in the Andijan region, species belonging to the Lamiaceae family are most often used by the local population for medicinal purposes, which is 25.7% of the total, followed by the Asteraceae (8.9%) and Apiaceae (6.9%) families. The species of these identified families are often used because of the greatest knowledge of them among the local population and the transmission of this information occurs from generation to generation. Keywords: Ferghana and Andijan regions, medicinal plants, traditional medicine, human diseases, herbal drugs, WHO, JASP, ArcGIS.